Danska och svenska binomiala uttryck – en jämförelse - Bönnemark, Margit (Nordiske Studier i Leksikografi, 2003)
Danska och svenska binomiala uttryck – en jämförelse In this paper, 369 Danish binomial phrases, defined as lexicalized phrases consisting of two words or phrases combined by og or eller, and characterized by a particular prosody and phonological, semantic, and/or syntactic resemblance, are analyzed. Furthermore, the relationship between 555 Danish binomial phrases with og and the 244 corresponding binomial phrases found in Swedish is also investigated. A group of 17 phrases with different preferred word order in the two languages is finally studied in depth. In the Danish and Swedish binomial phrases overall, factors such as frequency and length of elements, indicating degree of ‘markedness’, are of importance to determine word order, as proposed by Fenk-Oczlon (1989) and Sobkowiak (1993). Differences in word order in the smaller group cannot, however, be explained by these theories.